Tungsten oxide nanowire on copper surfaces: A DFT model - Sedivá, R. (2016)
We studied a model of a one dimensional tungsten oxide nanowire on a reconstructed Cu(110) surface by density functional theory calculations. The effect of oxygen vacancies on the electronic structure was analyzed (DOS). The nanowire equilibrium geometric configuration corresponds to tungsten oxide strips oriented along the Cu[110] direction, in which W-W distances are similar to the bulk data, in agreement with electron diffraction experiments. Bader charge analysis shows that the electron charge of the W atoms corresponds to a tungsten atom in the 6+ oxidation state. The presence of oxygen vacancies increases the electronic charge of the tungsten atoms. Formation of the oxygen vacancies by removal of terminal oxygen atoms is energetically favorable. Calculated PDOS shows stabilization of the tungsten states to lower energies due to the presence of oxygen vacancies.